2011
DOI: 10.1080/10401334.2011.586913
|View full text |Cite
|
Sign up to set email alerts
|

Global Longitudinal Pathway: Has Medical Education Curriculum Influenced Medical Students’ Skills and Attitudes Toward Culturally Diverse Populations?

Abstract: Clear and distinct differences between the two studied groups were found indicating the root of this increased confidence may have developed due to exposure to the Pathway program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Thirteen articles focused on the language barriers affecting clinical care. [108][109][110][111][112][113][114][115][116][117][118][119][120] Five of the interventions were longitudinal, seven of these interventions were 1-3 h, and one was two and a half weeks. Eight out of the 13 interventions were mandatory.…”
Section: Specific Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen articles focused on the language barriers affecting clinical care. [108][109][110][111][112][113][114][115][116][117][118][119][120] Five of the interventions were longitudinal, seven of these interventions were 1-3 h, and one was two and a half weeks. Eight out of the 13 interventions were mandatory.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Nevertheless, one article found that almost 40% of students failed to use interpreters in an encounter with a patient of limited English proficiency. 111 Zanetti et al 115 described a 4-year program that promotes cultural competency through civic engagement and second language fluency. Students who participated reported greater confidence in obtaining a medical history in a different language, advocating for the healthcare needs of underserved populations, and assessing the health beliefs and practice of patients from other cultures.…”
Section: Specific Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In health care, professional interpreters can be underused, with a reliance on untrained bilingual staff or family members leading to breaches of confidentiality and risks of inaccuracy . These may be minimised through training students in the use of interpreters in simulated settings using bilingual actors, and in real clinical settings …”
Section: Discussionmentioning
confidence: 99%
“… 1 , 11 - 16 Four previous studies involving the fourth author resulted in a wide range of findings connected to the effectiveness of a global multicultural pathway. 17 - 20 While some studies suggested no effect from multicultural education, 10 , 11 the most recent of the four studies found clear and distinct differences between two groups of students indicating the root of increased confidence in cultural competence may have developed from exposure to a specific multicultural pathway program with future research warranted to determine the impact of other similar experiences at the studied institution. All of these summarized research findings clearly indicate that a multi-modal approach to educating medical students about cultural competence and disparities in healthcare may be beneficial.We did not find any published studies analyzing a multicultural curriculum at a medical institution over a long period of time.…”
Section: Introductionmentioning
confidence: 99%